Relaxation Time Enhancement by Magnetic Dilution in Single-Molecule Magnets: An Ab Initio Study - Aravena-Ponce, D; Aravena-Ponce, D; Llanos-Silva, L; Llanos-Silva, L (Elsevier B.V., 2019)
Magnetic dilution is an effective strategy to enhance demagnetization times of Single-Molecule Magnets (SMMs). In this approach, a magnetic complex is co-crystallized with a diamagnetic analog to increase the distance between neighbor magnetic centers, diminishing the contribution of spin-spin dipolar interactions to demagnetization. In this article, we present an ab initio procedure to predict tunneling relaxation times (τQT) for magnetically diluted Single-Molecule Magnets. From a benchmark set of 18 mononuclear LnIII ions, it is concluded that the effect of magnetic dilution shows the same profile and a similar magnitude for all studied systems. For strongly diluted samples (i.e. 1% concentration), the model predicts and enhancement of around 4 orders of magnitude in τQT. Typical dilution proportions of 1:10 or 1:20 are associated by a ca. 100-fold increase in relaxation time. Variations in relaxation time were analyzed for three cases where experimental information for one dilution ratio is available. Furthermore, τQT at several magnetic ion concentrations were predicted for [Er(W5O18)2]9− and compared with literature data. In both cases, the agreement between experiment and theory was satisfactory, finding a general quadratic dependence on relaxation time enhancement upon magnetic dilution. © 2019